Of swords and shields: due process and crime control in times of globalization : liber amicorum prof. dr. J. A. E. Vervaele - Jong, Ferry de (Pompe reeks, 2023)
On 10 March 2023, John Vervaele retired as professor of Economic and European criminal law at Utrecht University. On the occasion of that farewell, this liber amicorum was presented to him. It comprises 85 contributions, written in a variety of languages by friends, colleagues and former colleagues from all over the world.00In keeping with the tradition of the Willem Pompe Institute for Criminal Law and Criminology, the contributions are arranged around the following themes, which have also been central to John's work: criminal justice, core values and human rights; crime, criminology and criminal justice; criminal justice and European integration; corporate crime and the enforcement of socio-economic law; and conflicts and transitional justice.00The contributions are very worthwhile for an academic audience, as well as for legal practitioners